Pendekatan Teknik Johari Window dalam Menangani Kesulitan Belajar Siswa Di SMP Al-Hidayah Medan - Ira Suryani; Muhammad Syukron Siregar (Universitas Islam Negeri Sumatera Utara Medan, 2020)
Abstrack: The problem in this study is the condition of learning difficulties experienced by students with research subjects of Medan Al-Hidayah Middle School students. This study aims to determine the implementation of the johari window engineering approach in dealing with student learning difficulties in Al-Hidayah Middle School Medan. This study used a qualitative method with the subject of the research counseling guidance teacher and 3 students of Al-Hidayah Medan Middle School. This study gives meaning that through the johari window technique approach can find out how the factors causing learning difficulties are either observed or experienced by students. The conclusion was proven through the results of observations and interviews obtained from 3 students and BK teachers. The result is students can provide an explanation of the level of learning difficulties experienced by students after being given a student approach shows a better attitude towards the approach that has been given by the teacher for guidance and counseling in overcoming student learning difficulties.Keywords: johari window technique, learning difficulties